Stomatal complexes of twenty-four species of Mimosa (Leguminosae) occurring in Mexico - Montaño-Arias, Susana Adriana; Camargo-Ricalde, Sara Lucía; Grether, Rosaura (Instituto de Ecología, A.C., 2018)
Background and Aims: The infrageneric classification of Mimosa (Leguminosae) is complex. Distinction among taxa is based on morphological and anatomical characters. Various authors have stated that the stomatal complexes are valuable in plant taxonomy. In Mimosa, since leaf anatomy has been poorly explored, the stomatal complexes of over 90% of its taxa are still unknown. Therefore, the objective of this study was to determine, with taxonomic purposes, the stomatal complex type of 24 taxa of Mimosa occurring in Mexico.Methods: Twenty-four taxa of Mimosa distributed in Mexico were selected. Per taxon, three individuals with similar height and coverage were chosen; a considerable amount of leaf pinnae was collected; pinnae were mixed in order to obtain a compound sample per taxon. Leaflets placed in the middle of the pinna were handpicked and washed with distilled water. Once the leaflets were cleared, they were dehydrated and permanent slides were prepared using synthetic resin.Key results: The study included three of the five sections of Mimosa. Section Batocaulon was the best represented, where most of the taxa belong to series Acanthocarpae and Boreales. Amphistomatic leaflets were found in 22 of the taxa; while the other two have hypostomatic leaflets. The 24 studied taxa present paracytic stomatal complexes; though M. goldmanii, M. luisana, M. monancistra, and M. pringlei var. pringlei, additionaly show the anisocytic type, except in M. benthamii var. benthamii, which presents the anomocytic type.Conclusions: The studied taxa were grouped considering three characters with taxonomic value: i) hypostomatic leaflets vs. amphistomatic leaflets, ii) the presence of only one type of stomatal complex vs. the presence of two types of stomatal complexes, and iii) paracytic and anisocytic stomatal complexes vs. paracytic and anomocytic stomatal complexes.